The Influence Of Organizational Culture, Organizational Commitment, And Organizational Communication On Employee Performance At PT. PLN (Persero) UP3 Sidoarjo - Fita Widi Rahmawati; Kumara Adji Kusuma; Rifdah Abadiyah; Sumartik Sumartik (UNIVED Press, 2024)
The increasing electricity demand requires electricity companies to achieve the specified targets in meeting stakeholder needs by improving the quality of Human Resources through various aspects. This study aims to determine the effect of organizational culture, organizational commitment, and organizational communication on employee performance at PT PLN (Persero) UP3 Sidoarjo. This research uses quantitative research. The population in this study were all employees of PT PLN (Persero) UP3 Sidoarjo as many as 95 employees. The sampling technique uses total sampling where all members of the population are taken as samples. The type of data used in this study is primary data obtained through distributing questionnaires and secondary data. The results of this study indicate that 1) organizational culture partially has a positive and significant effect on employee performance, 2) organizational commitment partially has a positive and significant effect on employee performance, 3) organizational communication partially has a positive and significant effect on employee performance, 4) organizational culture, organizational commitment, and organizational communication simultaneously have a positive and significant effect on employee performance at PT PLN (Persero) UP3 Sidoarjo